Sensor data monitoring software in android - Su, Rong (2016)
This dissertation introduces an Android app which is used for monitoring the sensor data. A sensor detects the gap of cylinder and the data will be sent to an Android embedded computer using Modbus protocol, to display on a 2D graph. The project will allow users to set the interval time to receive the gap sensor data. At any time, it can show the future gap trend on the 2D graph using the Least Square Method algorithm. When the gap value reaches 0.6 mm, it will generate both the alert message and voice. A sensor is used in this project to detect the distance variable and to provide a corresponding output, generally as an optical or electrical signal. Next, the signal is transformed into digital signal which can be analyzed and monitored easily. For the sake o f convenience, the data will be generated from a software. The hardware platform for data monitoring in this dissertation is the SONY L36H, 4.3 Android version. The software development environment is Android Studio, developed by Google Company. The simulated data is generated from Modbus Slave software, using TCP communication protocol. To achieve data conveying, both the devices have to be under the same network, namely, the same Wi-Fi, to get the same IP address.